Symbolic significance of newspaper titles: analysis of patterns in print newspaper titles in the digital age (Journal of Philosophy Culture and Political Science, 2021)
The titles of print newspapers around the world are culturally and politically diverse but have somecommon themes and patterns of logic. While the words Post, Times, Evening, Daily, News, Truth, andIndependent are among the most popular, creative variations of elements in titles reflect each newspaper’srecognizable identity on the global news map. Some titles refer to a unique historical legacy, somerepresent cultural values, others highlight specific geographic cities, states or areas, some titles signifythe concept of “freshness” of the news. This exploratory study aims to investigate the range of printnewspaper titles of seven representative countries – the United States, United Kingdom, France, Russia,Kazakhstan, India, and South Africa. Using grounded theory and textual and visual discourse analysis asmethods of newspaper titles, this study deliberately excluded all digitally born news outlets and focusedonly on titles that have originated from legacy news brands. By compiling and analyzing the online andprint slogans of approximately the top 50 newspapers from each country, this paper identifies certaintrends and distinctions among title and slogan choices.Key words: newspaper titles, google slogans, patterns of newspaper titles, Kazakhstan, USA, France,Russia, Great Britain, cultural meaning, symbolic significance.